Regional Income Convergence in Turkey: An Empirical Analysis from an Endogenous Growth Perspective - Bolkol, Hakki Kutay (Panoeconomicus, 2023)
This study analyzes convergence among regions of Turkey from an endogenous growth perspective. The results show that human capital, which is represented with R&D personnel, has a negative impact on economic growth in the regions based on its percentage in total employment. Moreover, we find that there is an estimated U-shaped relationship, which implies that if the percentage of R&D personnel in total employment increases after a certain level, the effect has a tendency of turning positive; the west region is especially closer to having a positive effect. However, regarding convergence, the relatively high-income west is closer to experiencing the positive effect of R&D personnel. Moreover, due to the relatively low percentage of R&D personnel in the east region, the economic growth of the east region is more negatively affected by R&D personnel. Therefore, using a strategy that is based on increasing the percentage of R&D personnel cannot help the east region to close the differences in income. JEL: O30, O47, O50, R11, R15.